The Rhetorical Rise and Demise of Democracy in Russian Political Discourse, Vol I The Path from Disaster Toward Russian Democracy - Williams, David Cratis (Academic Studies Press, 2021)
The 1983shootdown of KAL 007 and the 1986 Chernobyl nuclear accident dramatically changedthe Soviet Union in unpredictable ways. The Communist Party, which struggled tomaintain control of political messaging after the KAL crisis, lost control inthe aftermath of Chernobyl.